Children's environmental health in Central Asia and the Middle East - Carpenter, David O.; El-Qaderi, Saleh; Fayzieva, Dilorom; Gilani, Anwar H.; Hambartsumyan, Amelia; Herz, Katherine; Zaineh, Kamal (Taylor & Francis Ltd, 2006)
Children in Central Asia and the Middle East bear disproportionate environmental threats to health, of which the most widespread and serious result from poverty, malnutrition, lack of access to safe drinking water and food, and exposures to toxic chemicals. Their psychological health is threatened in several parts of this region by internal wars and strife. Many, or even most, children are regularly exposed to environmental tobacco smoke. In many of these countries, children constitute very high percentages of the population. Because children constitute the future, it is critical that these threats to their health be addressed and reduced to the greatest extent possible through both provision of safe and adequate drinking water and nutrition and reduction of exposures to environmental contaminants.
Keywords: lead; persistent organic pollutants; smoking; drinking water; Aral Sea; children; Asia; Middle East